Critical Study on Indonesian Criminal Law: Articles Related to Religious Protection in the Perspective of Maqashid Sharia - Sudarno Shobron; Moh. Abdul Kholiq Hasan; Muthoifin Muthoifin; Mukhtar Arifin (International Journal of Halal System and Sustainability, 2022)
This research is aimed to criticize four articles in Indonesian Criminal Law (KUHP) which have relation to religious protection using qualitative research method and maqashid Sharia analytic theory. This analytic theory is considered fit and proper to be used as critical study on articles in the criminal code. The result of this research shows that among the articles related to the religious guardian, some are still relevant to be applied in the law, some need clearer provisions and limitations, longer imprisonment period, and some need to be adjusted to current values. It is necessary that the criminal code have more active roles in establishing stability and harmony among different religious believers, maintaining the unity of the country in the frame of religious diversity. All those things are the actualization of why religion or maqashid Sharia is taught.